Di-(2-ethylhexyl) phthalate-induced tumor growth is regulated by primary cilium formation via the axis of H(2)O(2) production-thymosin beta-4 gene expression - Lee, Jae-Wook (Int J Med Sci, 2021)
Di-(2-ethylhexyl) phthalate (DEHP) that is one of the most commonly used phthalates in manufacturing plastic wares regulates tumorigenesis. Thymosin beta-4 (TB4), an actin-sequestering protein, has been reported as a novel regulator to form primary cilia that are antenna-like organelles playing a role in various physiological homeostasis and pathological development including tumorigenesis. Here, we investigated whether DEHP affects tumor growth via primary cilium (PC) formation via the axis of TB4 gene expression and the production of reactive oxygen species (ROS). Tumor growth was increased by DEHP treatment that enhanced TB4 expression, PC formation and ROS production. The number of cells with primary cilia was enhanced time-dependently higher in HeLa cells incubated in the culture medium with 0.1% fetal bovine serum (FBS). The number of cells with primary cilia was decreased by the inhibition of TB4 expression. The incubation of cells with 0.1% FBS enhanced ROS production and the transcriptional activity of TB4 that was reduced by ciliobrevin A (CilioA), the inhibitor of ciliogenesis. ROS production was decreased by catalase treatment but not by mito-TEMPO, which affected to PC formation with the same trend. H(2)O(2) production was reduced by siRNA-based inhibition of TB4 expression. H(2)O(2) also increased the number of ciliated cells, which was reduced by siRNA-TB4 or the co-incubation with CilioA. Tumor cell viability was maintained by ciliogenesis, which was correlated with the changes of intracellular ATP amount rather than a simple mitochondrial enzyme activity. TB4 overexpression enhanced PC formation and DEHP-induced tumor growth. Taken together, data demonstrate that DEHP-induced tumor growth might be controlled by PC formation via TB4-H(2)O(2) axis. Therefore, it suggests that TB4 could be a novel bio-marker to expect the risk of DEHP on tumor growth.